2009
DOI: 10.15448/1980-3729.2009.39.5850
|View full text |Cite
|
Sign up to set email alerts
|

Comunicação da saúde: um estudo comparado sobre a divulgação do câncer de mama Brasil-EUA

Abstract: Desde o ano de 1998, o dia 27 de novembro vem sendo comemorado no Brasil como o "Dia Nacional de Combate ao Câncer", momento em que campanhas de conscientização sobre a necessidade de prevenção desta doença são levadas à população. No último ano, 2006, chamou a atenção o fato de o tema escolhido ser a informação: "Câncer: a informação pode salvar vidas". Objeto de inúme-ros estudos científicos no Brasil e no mundo, o câncer de mama feminina foi o segundo tipo de câncer mais incidente sobre a população brasilei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Regarding cancer, the most investigated chronic disease, we found seven studies [12][13][14][15][16][17][18] , whose majority was conducted by the same researcher [13][14][15][16][17] . Part of them showed that the media gave more space to news about prevention [12][13][14]16 , although the focus on the coverage of scientific research was also present 12,17,18 . We found only one study on hypertension 19 .…”
Section: Chart 3 Characterization Of the Profile Of Physical Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Regarding cancer, the most investigated chronic disease, we found seven studies [12][13][14][15][16][17][18] , whose majority was conducted by the same researcher [13][14][15][16][17] . Part of them showed that the media gave more space to news about prevention [12][13][14]16 , although the focus on the coverage of scientific research was also present 12,17,18 . We found only one study on hypertension 19 .…”
Section: Chart 3 Characterization Of the Profile Of Physical Diseasementioning
confidence: 99%
“…Regarding comparative studies, there were few who used this feature; even those who analyzed more than one vehicle did not analyzed them in most cases in a comparative perspective. There were two studies, for example, that compared coverage in Brazilian and American newspapers, both related to cancer 15,18 . This methodology has been used in other areas of knowledge, but in the Communication, although the volume of research is high in relation to the news, few are comparative, showing that the number of journalism studies with this profile is low 86 .…”
Section: Newspaper: the Means Of Communication Most Investigatedmentioning
confidence: 99%